Actualización académica para Administradores Educativos en zonas de atención prioritaria, análisis de una experiencia - Ileana Vargas-Jiménez (Universidad Nacional, Costa Rica, 2007)
The author comments about a project that starts as a response for the updating requirement of administrative educational professionals who works in educational institutions located in poor communities. The project was developed in the provinces of San Jose and Heredia, through the PROMECUM program, working in coordination with the Public Department of Education.